SEQUENCING OF SIX GENOMES OF CLINICAL STRAINS OF NON-TUBERCULOUS MYCOBACTERIA - V. V. Ustinova; T. G. Smirnova; S. N. Аndreevskaya; I. Yu. Аndrievskaya; E. E. Larionova; L. N. Chernousova (Туберкулез и болезни лёгких)
.